Access to autonomous housing for beneficiaries of International Protection in Ireland - Keire Murphy; Amy Stapleton (The Economic and Social Research Institute (ESRI), 2024)
Housing plays a key role in the integration of beneficiaries of international protection (BIPs). However, past research has shown that BIPs often face significant barriers in accessing housing. Many countries provide supports to access autonomous housing as a result of this. These barriers pose a challenge for BIPs, who can find themselves with limited options to exit institutional or homeless accommodation, as well as for reception systems, which require outflow to accommodate new applicants. Understanding the challenges, barriers, and good practices is therefore a crucial element of the governance of accommodation of international protection applicants (IPA) in Ireland, as well as the integration of BIPs. However, there is limited recent research on the policies and supports in place for this group, their outcomes, and the challenges and barriers faced. This report considers the situation of those who arrived in Ireland, applied for international protection, and were granted this status. Applicants for international protection, beneficiaries of temporary protection (BOTP) fleeing the conflict in Ukraine, resettled refugees, and other third-country nationals residing in Ireland are outside of the scope of this study. The report is based on desk research, interviews, and stakeholder consultation.
Keywords: 330